The change in the control pattern of pressure extensions of the surface inclusive systems affecting the climate of Iraq during the rainy season 1950-2020 (Journal of Humanities and Social Sciences Research, 2023)
Drought is one of the natural hazards that threaten human societies and ecosystems، and although its effects do not come as sudden events such as floods and storms، it is considered a natural disaster that causes the greatest losses to human societies، and its importance lies in being a study that uses information technology and sensor systems in the study area of Through the satellite imagery of the study area، as this technique is characterized by its effectiveness and its ability to cover a wide area، in addition to observing the changes associated with the different land coverings، as it was found from a study that there is a similarity between the regions of Iraq in that most of the rains fall in the months of December and December for a second and exceed the amount falling during them More than 70٪ annually، and the decrease in the amount of rain during a certain period from the rate of precipitation during a period is considered a specific factor of drought، and according to the severity of the decline in the rainfall، where the SPI drought index can determine the severity of droughts at different time levels، which can be used، to estimate The intensity of the drought compares the value of the indicator، and determines the month where the value of the indicator is negative at the beginning of the drought، and the month where the value of the indicator is positive at the end of the drought The severity of dehydration was classified based on (SPI) to mild dehydration when the value of (SPI) was between 1.2 - 0.8 average، and between 1.3 - 1.5 severe between 1.6 - 1.9، and very severe dehydration when the value of (SPI) is less than - 2 while there is no Dryness when the value of (SPI) is greater than - 0.7.